1975
DOI: 10.1366/000370275774455518
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-Noise Ratio Comparison for Dispersive and Non-Dispersive Flame Atomic Fluorescence Measurements

Abstract: Signal-to-noise ratios achievable with dispersive and nondispersive atomic fluorescence systems are compared. In this comparison particular attention has been devoted to considerations affecting optimization of the dispersive system with low and high background flames. Relative signal and noise values are reported for Hg and Fe atomic fluorescence with dispersive, solar-blind nondispersive, and filter nondispersive systems with C2H2-air, separated C2H2-air, H2-air, and H2-O2-Ar flames. It is concluded that, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As pointed out by Vickers (11), flame background emission or fluorescence can be a serious limitation in nondispersive AFS. A sloping or changing background in the modulation interval will produce both f0 and 2/0 signal components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out by Vickers (11), flame background emission or fluorescence can be a serious limitation in nondispersive AFS. A sloping or changing background in the modulation interval will produce both f0 and 2/0 signal components.…”
Section: Resultsmentioning
confidence: 99%
“…Vickers (11) in a recent review has shown that there are some drawbacks to the use of a nondispersive system. Among these include the relatively low transmission of interference filters below 300 nm and the relatively low sensitivity of the R166 solar-blind photomultiplier tube compared to the more commonly used 1P28 photomultiplier tube.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Detec tion limits for about twenty elements including nickel were described by Larkins and Willis.6) The advantages and disadvantages of nondispersive atomic fluorescence spectrometry have been discussed by many workers. [5][6][7][8][9][10][11] According to the best of our knowledge, however, there has been no paper on the non dispersive atomic fluorescence spectrometric measurement of nickel using electrothermal atomization as well as on nickel determination in practical samples for either dispersive or non-dispersive modes. The difficulities seem to be that the high dissociation energy of nickel monoxide (4.2 eV) requires a high atomization temperature, which causes an significant increase of background noise level.…”
Section: Introductionmentioning
confidence: 99%